Decisions, resolutions and declaration (ACP BrusselsBE, 2008)
Presents two decisions; resolutions on bananas, cotton, sugar, fisheries, on WTO Doha Round of negotiations and on economic partnership agreements; as well as, the declaration on basic food prices and food security.
Keywords: TRADE